A Phase II Study of a Dose‐Density Regimen With Fluorouracil, Epirubicin, and Cyclophosphamide on Days 1 and 4 Every 14 Days With Filgrastim Support Followed by Weekly Paclitaxel in Women With Primary Breast Cancer. (30th January 2015) - Pietri, Elisabetta; Andreis, Daniele; Fabbri, Francesca; Menna, Cecilia; Schirone, Alessio; Kopf, Barbara; Rocca, Andrea; Amadori, Dino; De Giorgi, Ugo
Abstract : Background: Recent evidence shows that use of anthracycline and taxane adjuvant chemotherapy and dose‐dense regimens, consisting of more frequent administration of the drugs, have improved outcomes for breast cancer patients. In this study, we evaluated administration of an epirubicin‐based regimen with paclitaxel in a sequential, dose‐dense schedule as adjuvant treatment for patients with high‐risk primary breast cancer. Methods: In a phase II Simon two‐stage design study, we evaluated the feasibility of a modified fluorouracil, epirubicin, and cyclophosphamide (FEC) regimen at high dose intensity (fluorouracil 500 mg/m 2 i.v. on days 1 and 4, epirubicin 60 mg/m 2 i.v. on days 1 and 4, and cyclophosphamide 500 mg/m 2 i.v. on days 1 and 4; all drugs were administered every 14 days for 3 cycles) with granulocyte colony‐stimulating factor support followed by dose‐intense weekly paclitaxel 100 mg/m 2 for 8 cycles. In 11 patients with breast cancer following quadrantectomy ( n = 8) or modified radical mastectomy ( n = 3), any grade 3 (G3) or higher nonhematologic toxicity (excluding alopecia, nausea or vomiting, and bone pain, which might be a consequence of the administration of filgrastim) and adherence to the scheduled dose‐dense treatment (deliverability) were monitored with the purpose of enrolling an additional 27 patients in the case of a satisfying toxicity profile and deliverability of the planned treatment (at least 7 patients completing the treatment). Results: Five of 11 patients experienced G3 or higher nonhematologic toxicity during the FEC regimen. We did not observe G3 or higher nonhematologic toxicity related to paclitaxel treatment. In particular, three patients experienced G3 fatigue, one patient had G3 oral mucositis, three patients had G3 hypokalemia, one patient had G3 syncope, one patient had G3 transaminitis (alanine aminotransferase), one patient experienced G4 pulmonary thromboembolism, and 1 patient had a G3 breast infection. Four of 11 patients received the regimen with a 25% dose reduction of day 1 and 4 administrations of FEC. Seven of 11 patients required FEC delay ≥7 days in at least 1 cycle, regardless of dose intensity. Two patients failed to complete the FEC regimen. Two of the remaining 9 patients were treated with paclitaxel delay ≥7 days in at least one cycle. After a median follow‐up of 28 months, 9 patients were continuously disease free. Conclusion: The tolerability rate of a dose‐density regimen with FEC followed by weekly paclitaxel was considered not promising for completing the accrual of this study. Abstract : 摘要 背景 . 近期有证据显示蒽环类和紫杉烷类药物作为辅助化疗时，采用剂量密集方案、更频繁地给药，可改善乳腺癌患者的转归。本研究中，我们评价了一种辅助化疗方案在高危原发性乳腺癌患者中的应用，该方案为以表柔比星为基础、序贯紫杉醇治疗的剂量密集方案。 方法 . 本项II期研究采用 Simon 二阶段设计，评价了改良的氟尿嘧啶、表柔比星和环磷酰胺（FEC）方案的高剂量密度给药方案（氟尿嘧啶500 mg/m 2 ，第1、4天静脉注射；表柔比星60 mg/m 2 ，第1、4天静脉注射；环磷酰胺500 mg/m 2 ，第1、4天静脉注射；所有药物的给药周期均为14天，共3周期），同时给予粒细胞集落刺激因子支持，继以大剂量紫杉醇（100 mg/m 2 每周一次，共 8 周期）。11 例罹患乳腺癌后接受象限切除术（n = 8）或改良根治术（n = 3）的患者中，对任何发生≥3级的非血液学毒性（除外脱发、恶心或呕吐，以及骨痛，后者可能由于给予非格司亭导致）且依从剂量密集方案治疗计划（可实施性）的患者进行监测，旨在基于满意的毒性特征和计划治疗的可实施性方面的目的，再招募 27 例患者（至少 7 例患者完成治疗） 结果 . 5/11例患者在接受 FEC 方案治疗过程中发生≥3级非血液学毒性事件。我们并未观察到与紫杉醇治疗相关的≥3级非血液学不良事件。详细情况为：3 例发生 3 级疲乏、1 例发生 3 度口腔黏膜炎、3 例发生 3 级低钾血症、1 例发生 3 级晕厥、1 例发生 3 级转氨酶（丙氨酸氨基转移酶）水平升高、1 例发生 4 级肺血栓栓塞、1 例发生 3 级乳腺感染。4/11 例患者接受的 FEC 方案在第 1、4 天给药时剂量下调 25%。7/11 例患者至少在 1 个周期中 FEC 方案给药需要延迟≥7 天，无论为何种给药剂量强度。2 例患者未完成 FEC 方案。其余 9 例患者中，2 例至少在 1 个周期中紫杉醇给药需延迟≥7 天。中位随访 28 个月后，9 例患者保持无病状态。 结论 . 我们认为 FEC 剂量密集方案继以每周一次紫杉醇方案的耐受率对于本研究继续招募患者并不乐观。 The Oncologist 2015;20:239–240